Gaya Bahasa Kiasan dalam Kutipan BAB Tanda-Tanda Cinta dari Ṭawq al-Ḥamāmah karya Ibn Ḩazm - Myrna Nur Sakinah; Elza Salsabillah Arriyaha Lawaqih Taufik (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
This study aims to analyze the use of figurative language in the chapter “Signs of Love” in Ibn Hazm's Ṭawq al-Ḥamāmah. The main focus of this research is to identify and examine the forms of figurative language including simile, metaphor, and personification, which are used to describe various expressions and symptoms of love. This research uses a descriptive qualitative approach, with data collection techniques in the form of reading and note-taking of relevant quotations in the source text. The results of the analysis show that Ibn Hazm uses simile 13 times, metaphor 2 times, and personification 4 times. Ibn Hazm uses this variety of figurative language styles to convey the experience of love in a way that is full of meaning and touches feelings.